Fungal Chitosan-Derived Biomaterials Modified with Kalanchoe pinnata as Potential Hemostatic Agents—Development and Characterization - Radwan-Pragłowska, Julia (Polymers (Basel), 2021)
Massive blood loss is still a great challenge for modern medicine. To stop the hemorrhage during the surgery or after injury apart from suturing or electrocoagulation, the most efficient method of hemostasis restoration is the use of hemostatic agents. Although there are numerous products on the market, there is still a need for biomaterials that are capable of fast and efficient bleeding management without affecting wound closure or embolism. Chitosan is known for its hemostatic activity; however, its quite poor mechanical properties and heterogenous chemical composition still needs some improvements to become superior compared to biological adhesives. The following study deals with the preparation and evaluation of chitosan-derived natural biomaterials containing Kalanchoe pinnata extract with the potential application as a blood-clotting agent. The materials were obtained under microwave-assisted conditions in two different forms (granules/dressing), whose chemical structure and morphology were studied. Their antioxidant properties have been proven. The chitosan-derived hemostatic agents exhibited superior blood sorption abilities and lack of cytotoxicity to L929 mouse fibroblasts. The study also showed the differences in biological properties depending on their preparation method. The potential mechanism of action was proposed as well as their potential in hemostasis revival.